Investigation of anthraquinone-producing Trichoderma reesei by highperformance liquid chromatography (HPLC) - Zeyad Khalaf Hussein; Ghada Basil Alomashi; Khalied Yassen Zakair (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the isolates of Trichoderma that produce anthraquinones by High-performance Liquid Chromatography (HPLC). Methods: Trichoderma specimen were collected from Wassit Soil and identified dependent on morphological features and tested for production of anthraquinones by HPLC, Trichoderma isolate which produced a high concentration of anthraquinones diagnosed for the species using PCR-ITS region. Results: Ten isolates were identified as Trichoderma according to morphological and microscopic features. Results three Trichoderma isolates show differences between the concentrations of anthraquinones among the ten isolates. The total concentration of this compound in the extracts of specimens 1, 2 and 3 were (7.765ug/ml), (2.308ug/ml), and (4.977ug/ml) respectively. At the final concentration of Trichoderma isolates, genomic DNA have been extracted (400 to 600 ug) / (2 to 3g) fresh mycelium, and with a concentration of (1.6 to1.8), and the results of amplifying Trichoderma DNA samples by using ITS-1 and ITS-4 showed a single unique band consistent with T. reesei F48-03, Which with other isolates of the Trichoderma were missing, were identified successfully. Conclusion: For identification and phylogenetic classification of Trichoderma, DNA-based methods that provide useful classification information are presently used. For several years, most T. spp. is regarded as a single species due to their morphological similarity. This research used ITS markers to distinguish genotypes within T. spp. because of amplifying a distinct, naturally determined locus with a couple of T.reesei -specific oligonucleotide primers. This research was carried out to provide supporting evidence for the long-standing antimicrobial use of anthraquinone. Keywords: DNA, Primers, Trichoderma, Phylogeny, Soil, Chromatography, Liquid, Polymerase, Reaction, Anthraquinones, Mycelium, Plant, Genomics.